Molecular hydrogen formation on interstellar PAHs through Eley–Rideal abstraction reactions. Issue 1 (11th June 2018) - Foley, Nolan; Cazaux, S; Egorov, D; Boschman, L M P V; Hoekstra, R; Schlathölter, T
ABSTRACT: We present experimental data on H2 formation processes on gas-phase polycyclic aromatic hydrocarbon (PAH) cations. This process was studied by exposing coronene radical cations, confined in a radio-frequency ion trap, to gas-phase H atoms. Sequential attachment of up to 23 hydrogen atoms has been observed. Exposure to atomic D instead of H allows one to distinguish attachment from competing abstraction reactions, as the latter now leave a unique fingerprint in the measured mass spectra. Modelling of the experimental results using realistic cross-sections and barriers for attachment and abstraction yield a 1:2 ratio of abstraction to attachment cross-sections. The strong contribution of abstraction indicates that H2 formation on interstellar PAH cations is an order of magnitude more relevant than previously thought.